The Organization of Biosphere Compatibility Construction : Justification of the Predictors of Building Development and the Implementation Prospects - Ishchenko, Tatyana; Chupryna, Yuri; Pokolenko, Vadym (International Journal of Engineering and Technology, 2018)
Taking into account the global trends allows us to assert that during the next decades, and especially during the first half of the XXI century, there will be a significant increase in the volumes of materials and energy sources involved in the production process.The main components of sustainable development of society are defined: economic, ecological and social. It is proved that the economic system is an integral part of the complex sustainable development of the territory, to achieve which all its fields should be balanced.It has been established that in order to achieve and maintain a high quality of life of the population and the quality of the environment, it is necessary to adhere to certain basic principles in the economic and technological spheres.Â